Mechanization in Cotton – An Overview - Ramanjaneyulu, A. V.; Swetha, D.; Sudarshanam, A.; Reddy, R. Uma (Chronicle of Bioresource Management, 2023)
Cotton is an important cash crop for Indian farmers and plays an important role in the economy of the country. Maximizing production and productivity while minimizing the cost continues to be a great challenge in view of increasing demand for cotton on one hand and increasing labour shortage and cost on the otherhand. Hence, mechanization in cotton cultivation will play a key role in reducing the cost and time. It envisages use of various power sources and improved farm tools and equipment to reduce the drudgery of the human beings and draught animals, achieving precision and timeliness in efficient utilization of various inputs thus reduce the losses. It involves partial or full replacement of traditional human and animal energy by engine-driven equipment. It also enhances energy use efficiency and productivity. The various machinery that can be used for different agronomic operations during pre and post harvest crop period are discussed in the article.